Intraoral ultrasonography of tongue mass lesions - Sugawara, Chieko; Takahashi, Akira; Kawano, Fumiaki; Kudo, Yasusei; Ishimaru, Naozumi; Miyamoto, Youji (Dento-maxillo-facial radiology, 2016)
To demonstrate the usefulness of intraoral ultrasonography (IOUS) for tongue mass lesions, we analyzed surgery cases excluding squamous-cell carcinoma and leukoplakia and compared IOUS and pathological findings. We used the hospital information system and Radiology Information System to evaluate the IOUS and pathological findings of patients who underwent surgeries for tongue masses in the past 11 years. Surgeries for the tongues were performed in 268 cases. Imaging examinations were carried out in 52 (19.4%) cases including 42 (15.7%) cases by IOUS. The pathological results of the surgeries were as follows: 36 cases were inflammatory lesions, 74 cases were tumours, 131 cases were hyperplasia, 8 cases were cystic lesions and 19 cases were other miscellaneous lesions. On the other hand, the number of patients who received IOUS in the same period was 87, and 42 of them had surgeries. In 32 out of the 42 (76.2%) cases, pre-operative IOUS features matched with pathological results. Most of the haemangiomas and lipomas could be diagnosed by IOUS alone. IOUS of the tongue revealed the nature of the lesions including the border, size, location, depth, the presence or absence of a capsule and the internal structure including vascularity of the mass. The ultrasonographic findings well reflected the histological findings. IOUS is a simple and useful technique that provides additional information beyond inspection, clarifying the internal structure, blood flow and relationships with the adjacent tissues. In this article, we indicated 11 representative cases (fibrous polyp, haemangioma, pyogenic granuloma, lipoma, liposarcoma, chondroma, lymphangioma, schwannoma, neurofibroma, pleomorphic adenoma and amyloidosis) to show the usefulness of IOUS.